A Systematic Review of Clinical Trials on the Efficacy and Safety of CRLX101 Cyclodextrin-Based Nanomedicine for Cancer Treatment - Ana Serrano-Martínez; Desirée Victoria-Montesinos; Ana María García-Muñoz; Pilar Hernández-Sánchez; Carmen Lucas-Abellán; Rebeca González-Louzao (MDPI AG, 2023)
CRLX101 is a cyclodextrin-based nanopharmaceutical designed to improve the delivery and efficacy of the anti-cancer drug camptothecin. Cyclodextrins have unique properties that can enhance drug solubility, stability, and bioavailability, making them an attractive option for drug delivery. The use of cyclodextrin-based nanoparticles can potentially reduce toxicity and increase the therapeutic index compared to conventional chemotherapy. CRLX101 has shown promise in preclinical studies, demonstrating enhanced tumor targeting and prolonged drug release. This systematic review followed PRISMA guidelines, assessing the efficacy and toxicity of CRLX101 in cancer treatment using clinical trials. Studies from January 2010 to April 2023 were searched in PubMed, Scopus, Web of Science, and Cochrane Database of Systematic Reviews, using specific search terms. The risk of bias was assessed using ROBINS-I and Cochrane risk-of-bias tools. After screening 6018 articles, 9 were included in the final review. These studies, conducted between 2013 and 2022, focused on patients with advanced or metastatic cancer resistant to standard therapies. CRLX101 was often combined with other therapeutic agents, resulting in improvements such as increased progression-free survival and clinical benefit rates. Toxicity was generally manageable, with common adverse events including fatigue, nausea, and anemia.